RUSSIA AND THE WEST: A ROADMAP TO COOPERATION THROUGH FOREIGN POLICY LINKAGE OF MIDDLE EAST AND EASTERN EUROPE - L. D. Owen (Vestnik MGIMO-Universiteta)
The article discusses the current state of relations between Russian and the West. The author presents long-term assessment of rising tensions between Russia and the West. The article identifies the NATO expansion as one of the most important factors that contributed to the current deterioration. The author argues that the NATO expansion was a political miscalculation of the Western countries. The author believes that the relations between Russia and the West can be improved through foreign policy linkage of two regions: Middle East and Eastern Europe. It is the place for significant political transformations (especially in the Middle East) and both sides are politically involved there. The first major recent shift in the global political landscape there is Russian-Syrian alliance that has changed the development of the civil war in the country as well as global counterterrorist efforts. The second major shift occurs in the Saudi Arabia where a more moderate leadership has come to power. The author proposes the diplomatic framework for improving relations 5+1 format that includes the USA, major European states and Russia. However, the main issue is not the format of negotiations, but its essence. Russia could use its current potential as a mediating power to fully restore the Syrian state and calm down the tensions between Saudi Arabia and Iran. In return, the West can be more flexible in conflicts in the postSoviet space.